Two new triterpenoids from the roots of Pinus densiflora. Issue 3 (4th March 2017) - Otaka, Junnosuke; Komatsu, Masabumi; Miyazaki, Yasumasa; Futamura, Yushi; Osada, Hiroyuki
Abstract: Chemical investigation of the roots of Pinus densiflora led to the isolation of two new triterpenoids, (24 S )-3 β -methoxy-24, 25-epoxy-lanost-9(11)-ene (1) and 29-acetoxy-3 α -methoxyserrat-14-en-21 α -ol (2), together with three known serratene-type triterpenoids (3–5) and four known diterpenoids (6–9). Their structures were determined by spectroscopic analyses.